Art and Psychological Well-Being: Linking the Brain to the Aesthetic Emotion - Mastandrea, Stefano; Fagioli, Sabrina; Biasi, Valeria (Frontiers in Psychology, 2019)
Empirical studies suggest that art improves health and wellbeing among individuals. However, how aesthetic appreciation affects our cognitive and emotional states to promote physical and psychological wellbeing is still unclear. In this review, we consider the idea that the positive emotional output elicited from the aesthetic experience affects mood, and indirectly promotes health and wellbeing. First, we examine evidence that arts promoting wellbeing involve art museums, healthcare settings, and education. Second, we review some neuroimaging studies addressing aesthetic experience and emotional processing. In particular, we leveraged advances in neuroaesthetics to explore different hypotheses about the determinants of aesthetic pleasure during art reception, in the attempt to clarify how experiencing art promotes wellbeing. Finally, we propose research on aesthetic experience and psychophysiological measures of stress, with the goal of promoting a focused use of art as a tool for improving wellbeing and health.